Color and COD removal from wastewater containing Reactive Black 5 using Fenton’s oxidation process - Meriç, Süreyya; Kaptan, Deniz; Olmez, Tuğba (Elsevier BV, 2004)
In this study, Reactive Black 5 (RB5) was removed from synthetic wastewater using Fenton's oxidation (FO) process. Experiments were conducted on the samples containing 100 and 200 mg l(-1) of RB5 to remove the dye toxicity. Seventy-five milligram per litre of RB5 caused 25% toxicity on 24-h born daphnids whereas 100 mg l(-1) of RB5 displayed 100% toxicity on Daphnia magna. The study was performed in a systematic approach searching optimum values of FeSO(4) and H(2)O(2) concentrations, pH and temperature. Optimum pH and temperature for 100 mg l(-1) of RB5 were observed as 3.0 and 40 degrees C, respectively, using 100 mg l(-1) of FeSO(4) and 400 mg l(-1) of H(2)O(2) resulted in 71% chemical oxygen demand (COD) and 99% color removal. For 200 mg l(-1) of RB5, 84% COD removal was obtained using 225 mg l(-1) of FeSO(4) and 1000 mg l(-1) of H(2)O(2) yielding 0.05 molar ratio at pH 3.0 and 40 degrees C. Color removal was also more than 99%. The optimum conditions determined in accordance with the literature data. The H(2)O(2) requirement seems to be related to initial COD of the sample. FeSO(4)/H(2)O(2) ratios found were not changed for both concentrations. The temperature affected the COD removal significantly at high degrees. Toxicity was completely removed for each concentration of RB5 at optimum removal conditions.
Keywords: Iron; Temperature; Color; Hydrogen Peroxide; Hydrogen-Ion Concentration; Oxygen; Kinetics; Daphnia; Naphthalenesulfonates; Animals; Coloring Agents